The cost of non-Europe, revisited. (6th May 2019) - Mayer, Thierry; Vicard, Vincent; Zignago, Soledad
Summary: In this paper, we quantify the "Cost of Non-Europe", that is, the trade-related welfare gains each country member has reaped from the European Union (EU). Thirty years after the terminology of Non-Europe was used to give estimates of the gains from further integration, we use modern versions of the gravity model to estimate the trade creation implied by the EU, and apply those to counterfactual exercises where for instance the EU returns to a "normal, " shallow-type regional agreement, or reverts to WTO rules. Those scenarios are envisioned with or without the exit of the United Kingdom from the EU (Brexit) happening, which points to interesting cross-country differences and potential cascade effects in doing and undoing of trade agreements.